2020
DOI: 10.17576/pengurusan-2020-58-05
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Foreign Exchange Exposure and Shariah-compliant Status on Malaysian Firms’ Hedging Practice

Abstract: This study investigates the impact of foreign exchange (forex) exposure and Shariah-compliant status on firms' decision to practise hedging. It employs panel multiple and multinomial logistic regression on 702 firm-year observations from 117 non-financial listed firms over the period from 2010 to 2015. The sample consists of 70% Shariah-compliant firms, representative of the 74%-85% Shariah-compliant firms listed on Bursa Malaysia during the study period. From the multinomial logistic regression, this study fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 42 publications
0
3
0
4
Order By: Relevance
“…This study utilizes Malaysian data as Malaysia is the leading country in Islamic finance and having the most advanced Islamic capital market (Ledhem and Mekidiche, 2020). Nevertheless, hedging practices among its SCFs are still not well explored and very much lag behind against firms in the developed countries (Wahab et al , 2020). Furthermore, the awareness of derivatives among firms is still low and most managers do not understand the function and the importance of derivatives as a hedging instrument (Ameer et al (2011)) and Islamic hedging is still limited due to the lack of awareness on Islamic hedging and poor documentation of Islamic hedging in annual reports of firms (Mohamad et al , 2014).…”
Section: Data and Research Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…This study utilizes Malaysian data as Malaysia is the leading country in Islamic finance and having the most advanced Islamic capital market (Ledhem and Mekidiche, 2020). Nevertheless, hedging practices among its SCFs are still not well explored and very much lag behind against firms in the developed countries (Wahab et al , 2020). Furthermore, the awareness of derivatives among firms is still low and most managers do not understand the function and the importance of derivatives as a hedging instrument (Ameer et al (2011)) and Islamic hedging is still limited due to the lack of awareness on Islamic hedging and poor documentation of Islamic hedging in annual reports of firms (Mohamad et al , 2014).…”
Section: Data and Research Methodologymentioning
confidence: 99%
“…Besides, they have argued that conventional derivatives should not be used in Islamic finance for hedging due to the conventional finance practicing derivatives for speculation. Beside, Wahab et al (2020) employed logistic regression and found that FCDs are significant in predicting hedging among the SCFs in Malaysia.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Pengujian terhadap interaksi antara lindung nilai dengan risiko FX (lindung nilai x risiko FX) akan memastikan derivatif FX yang digunakan adalah untuk tujuan menguruskan risiko FX. Berikutan perlaksanaan FRS 7 dan 139, kajian ini dapat menggunakan aliran tunai asing (FCF) sebagai ukuran risiko FX seperti beberapa kajian terkini (Lily et al 2017;Wahab et al 2019Wahab et al , 2020Wahyudi et al 2019).…”
Section: Pendahuluanunclassified
“…Dengan wujudnya alternatif derivatif FX Islam ini, syarikat di Malaysia sepatutnya lebih berhatihati dalam memilih instrumen demi mengekalkan status patuh Shariah mereka. Namun berdasarkan dapatan analisis Wahab et al (2020), kebarangkalian syarikat patuh Shariah di Malaysia menggunakan instrumen derivatif FX konvensional adalah lebih tinggi berbanding syarikat yang tidak patuh Shariah. Oleh itu, terdapat kebarangkalian majoriti syarikat patuh Shariah di Malaysia mengamalkan instrumen lindung nilai konvensional, konsisten dengan dapatan dan Shaari (2018).…”
Section: Pendahuluanunclassified
“…Arif, Muda, Alam and Mohamad (2019) reported one of the key concerns that could threaten Islamic risk management tools in the financial market is the attitude of managers in relying on the current structure of conventional instruments. Additionally, hedging practices among Shari'ah-compliant Malaysian firms are underexplored and lag behind firms in developed countries (Wahab et al, 2020). Mohamad et al (2014) reported that although firms are categorised as Shari'ah-compliant firms, their risk management in dealing with market uncertainties remains at the infancy stage with limited use of hedging instruments.…”
Section: Introductionmentioning
confidence: 99%